Habilitacje w Polsce Ludowej. Część 2. Warunki i przebieg habilitacji w prawie o stopniach i tytułach naukowych - Wojtczak, Krystyna (Studia Prawa Publicznego, 2019)
Habilitation proceedings ending with a conferral of an academic degree were first introduced in the Polish People’s Republic by virtue of the Act on higher education of 1958. The academic title of docent, which the Act also provided for, was later endorsed by the Act of 1965 on academic titles and academic degrees. Another academic degree of ‘habilitated doctor’ (doktor habilitowany) functioned from 1968 and continued through subsequent legislative acts in force until 1990 as well as through the years after later reforms. The changes in higher education implemented in 1965–1990 were not fi nal and continued to be modifi ed in the following areas: (1) the branches and science and disciplines in which the academic degrees of docent or doktor habilitowany could be conferred; (2) the requirements which institutions (establishments of higher education, research units of the Polish Academy of Sciences and other research entities) had to fulfi l before earning the rights to confer the academic degrees referred to above; (3) establishment of the lists of institutions entitled to confer these academic degrees. The solutions then adopted were by no means triggered by the intention to replace the academic degree of docent with a degree of doktor habilitowany. On the contrary, the majority of changes, of which those happening after 1985 were even more politically biased, did not refl ect any legal need but aimed at restricting the autonomy of schools of higher education in the scope of conferring academic degrees. This tendency extended to the conditions of commencing habilitation proceedings and the very course of the proceedings. As of 1985 one of the requirements of the key factors qualifying successful candidates was an ‘impeccable civic attitude.’ After 1985, most of the activities which had been till then conducted by committees appointed Faculty councils, were to be taken up by the relevant councils, although the latter were allowed to appoint from time to time committees to perform some of the activities related to habilitation proceedings. The Act of 1965 abandoned the requirement of the candidate’s habilitation lecture, re-established in 1985.